Search for dark matter in events with a leptoquark and missing transverse momentum in proton-proton collisions at 13 TeV; Physics Letters B; Vol. 795 - Sirunyan А. М.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Asilar E. Ece; Bergauer T. Thomas; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2019, 2019)
Title screen